Evaluation of hysterosalpingography findings in women with infertility - Shermin, Shahana; Noor, Aysha; Farjana, Shayla; Begum, Monowara (BIRDEM Medical Journal, 2024)
Background: Hysterosalpingography (HSG) helps in diagnosis of uterine and fallopian tube abnormalities. Use of HSG in investigating infertile women may provide important information useful to the gynaecologists during treatment planning. The aim of this study was to review the pattern of HSG findings in patients being advised to do the investigation for infertility evaluation. Methods: This cross-sectional observational study included 150 patients undergoing HSG at Popular Diagnostic Centre, Shantinagar, Dhaka, Bangladesh from March to October 2022. All the patients were duly counseled and a written informed consent was obtained. The HSGs were performed between the 7th and 11th day of the menstrual cycle with iodine containing water-soluble contrast media iohexol (Imiro™). A non-steroidal antiinflammatory drug (NSAID) was given 20 minutes prior to the procedure. All the patients were given prophylactic antibiotic. The clinical data and radiological findings were tabulated and analyzed. Results: The age of the infertile women ranged between 18 and 45 years, with a mean ± SD of 28.18 ± 5.69 years. Majority of the patients (73.3%) were referred due to secondary infertility and 32.72% of them were from 25-29 years group. The mean ± SD duration of marriage (in years) was 7.9 ± 4.3 and that of subfertility (in years) was 4.4 ± 2.8. HSG revealed either uterine or tubal pathology in 34.7% patients and 3.3% patients had abnormalities in both uterus and fallopian tubes. The commonest abnormality reported was bilateral tubal blockade in 19 patients, 4 in primary subfertility and 15 in secondary subfertility patients. Uterine abnormalities were observed in 8.7% patients and arcuate uterus was the commonest (4.70%) finding. Conclusion: HSG revealed either uterine or tubal pathology in one-third of patients and 3.3% patients had abnormalities in both uterus and fallopian tubes. Uterine abnormalities were also detected in 8.7% of the study subjects. Wide and wise application of HSG can avoid the practice of unnecessary and sometimes more aggressive procedures in evaluation of women with infertility. BIRDEM Med J 2024; 14(1): 3-9